Immunogenicity of sequential inactivated and oral poliovirus vaccines (OPV) versus inactivated poliovirus vaccine (IPV) alone in healthy infants: A systematic review and meta-analysis. Issue 11 (2nd November 2018) - Tang, Guihua; Yin, Wen; Cao, Youde; Tan, Liming; Wu, Shuyu; Cao, Yudong; Fu, Xianyong; Yan, Jing; Jiang, Xingjun
ABSTRACT: Background: The emergence of vaccine-associated paralytic poliomyelitis has become an ongoing burden of poliomyelitis. During this special period from OPV to IPV-only immunization schedule, we did a meta-analysis to compare the immunogenicity of sequential IPV and OPV versus IPV alone in healthy infants. Methods: This systematic review and meta-analysis was registered at international prospective register of systematic reviews (PROSPERO), and the number was CRD42017054889. We performed it as described. Results: Finally, 6 articles were qualified for our review. The results showed that seroconversion rates against all 3 serotype polioviruses were non-inferior and Geometric mean antibody titers (GMTs) were superior in sequential schedules compared with IPV-only schedule. Thus, the sequential vaccination schedules could induce a stronger immunogenicity. Conclusions: To decrease vaccine-associated and vaccine-derived poliomyelitis, it is a reasonable option to select sequential schedules during this special transition from OPV to IPV-only immunization schedule, which coincides with the current WHO recommendations.